An Ayurvedic Approach of Ahiputana with Special Reference to Napkin Dermatitis: A Literature Review - Umang Varshney; Sachin Bhagwat; Geetika; Shubham Gupta (International Journal of Ayurveda and Pharma Research, 2024)
Ahiputana is mentioned in Kshudraroga in Ayurveda. A mother who neglects her child may cause them to suffer from a variety of illnesses, among them is Ahiputana. Diaper dermatitis, also known as napkin dermatitis, is one of the most prevalent skin ailments in young children and infants. Pediatric OPD frequently deals with Ahiputana, also known as napkin dermatitis. The Guda region (Napkin region) is home to several diseases that are described in the Ayurved Samhita, including Ahiputana, Anamika, Sannirudhguda, Parikartika, Gudabhransh, and Gudakutta. All Samhita’s explained Ahiputana as a skin condition that primarily affects the Pitta, Kapha, and Rakta doshas and is typically observed in young children and newborns. Poor hygiene and sweat retention causes ammonia to build up, which causes blistering rashes in the skin of anal area. According to the Ayurvedic Samhita, one of the causes of Ahiputana is stanyadushti. Depending on the Doshas involved and the state of the rash, the treatment plan may include avoidance of causes, Stanya shodhana, local applications, decoctions for cleaning, powders for dusting, and other methods. A deeper understanding of napkin dermatitis and Ahiputana will undoubtedly pave the way for the creation of better management guidelines that can provide newborns with a great deal of relief. As a result, this paper presents a complete evaluation of Ahiputana and Napkin dermatitis.